Teachers' roles in second language learning : classroom applications of sociocultural theory - Yoon, Bogum; Kim, Hoe Kyeung (Research in second language learning., 2012)
This book is designed to provide practical applications of sociocultural theory with regard to teachers' roles in second language education. By providing specific examples of teachers' roles in the classroom, the book aims to help researchers, teacher educators, and classroom teachers make clear connections between practice and theory in second language learning. All the studies in this edited book are conducted in the PreK-16 classroom setting. Each chapter presents rigorous research analysis within the framework of sociocultural theory and provides rich descriptions of teachers' roles.The book is intended to be used in teacher education courses. The primary audience of the book is in-service teachers who work with second language learners (SLLs) in their classrooms including ESL/Bilingual classrooms or regular classrooms. Since many SLLs receive instructions both in the ESL/Bilingual classrooms and in the regular classrooms, it is important to discuss teachers' roles in both settings. The secondary audience of the book is teacher educators and researchers who work with pre-service and in-service teachers in teacher education. This book will be an excellent resource for book study groups and practitioners working with professional learning communities.